Invoking Hope : Theory and Utopia in Dark Times - Wegner, Phillip E., 1964- (Book collections on Project MUSE., 2020)
"Invoking Hope: Reading Theory and Utopia in Dark Times argues for the undiminished importance of the practices of theory, utopia, and deep, close, and even critical reading in our current situation of what Brecht refers to as finsteren Zeiten, dark times. Written during 2016, an extraordinarily consequential year, Wegner reflects on the question: what does any particular theory allow us to do, what is the value of so doing, and, most importantly, who benefits?"--